2019
DOI: 10.1007/s40519-019-00740-6
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of mindful eating on the relationship between emotional functioning and eating styles in overweight and obese women

Abstract: The aim of the current study was to examine the moderating effect of mindful eating on the relationship between emotional functioning and eating styles in overweight and obese women. Methods One hundred and eighty four overweight and obese adult women (BMI 30.12 ± 3.77 kg/m 2) were assessed with the Difficulties in Emotion Regulation Scale, the Positive and Negative Affect Schedule, the Three Factor Eating Questionnaire and the Mindful Eating Scale. Results Mindful eating significantly moderated several of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 63 publications
(103 reference statements)
3
26
1
2
Order By: Relevance
“…Trauma, ED symptoms and BD were all associated directly with BMI, underscoring the complex web of influences between these variables. Most people tend to under- or overeat when distressed, and emotional difficulties can lead either to high BMI ( Czepczor-Bernat et al, 2019 ) or to low BMI, as in restricted EDs ( Farrington et al, 2002 ) Such alternative patterns make linear associations difficult to find, and path analysis can offer a clearer picture. Furthermore, when participants were divided into high, intermediate and low BMI groups, significant differences were observed only for disordered eating (ED symptoms) and BD, replicating the findings for linear correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma, ED symptoms and BD were all associated directly with BMI, underscoring the complex web of influences between these variables. Most people tend to under- or overeat when distressed, and emotional difficulties can lead either to high BMI ( Czepczor-Bernat et al, 2019 ) or to low BMI, as in restricted EDs ( Farrington et al, 2002 ) Such alternative patterns make linear associations difficult to find, and path analysis can offer a clearer picture. Furthermore, when participants were divided into high, intermediate and low BMI groups, significant differences were observed only for disordered eating (ED symptoms) and BD, replicating the findings for linear correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Among overweight and obese women, emotional eating is positively associated with both emotion dysregulation and negative affect; however, mindful eating does not buffer the impact of emotional dysregulation and negative affect on emotional eating [34]. Those results suggest that food loses its original energy function and serves to satisfy emotional comfort.…”
Section: Introductionmentioning
confidence: 87%
“…Several other trials on mindfulness in weight management are ongoing [90-92] (Table 2). Recent studies conducted in this area, which were not included in the reviews and meta-analyses above described, are shown in Table 3 [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. Sixteen studies were retrieved, including 9 RCTs and 7 intervention studies without a control group.…”
Section: Studies On Mindfulness-based Interventions and Weight Managementmentioning
confidence: 99%
“… Levin, 2020 [ 95 ] RCT Adults with overweight and obesity 79 n =39: ACT on health online course and coaching calls n =40: waiting list Participants in the ACT condition improved significantly the healthy eating index and the outcomes assessing self-reported eating behaviors, weight, mental health, weight self-stigma, and psychological inflexibility A greater improvement on self-reported weight was found in participants assigned to ACT condition than the waiting list. Czepczor-Bernat, 2020 [ 96 ] Intervention study Adult women with overweight and obesity 184 n =184 mindful eating Mindful eating was a significant moderator for emotional eating, and restrictive eating, but not for uncontrolled eating; mindful eating was a significant moderator for the relationship between negative emotions and emotional eating, restrictive eating, and uncontrolled eating - Felske 2020, [ 97 ] Proof-of -concept intervention study Adults with obesity seeking bariatric surgery 56 n =56: MII sessions with cognitive, behavioral, and psychoeducational components Improvements in addictive-like eating, binge eating, emotional eating, and grazing were observed from pre- to post-MII and at 12-week follow-up - Schnepper, 2019 [ 98 ] RCT Individuals motivated to improve their eating behavior or lose weight 46 n =23: mindfulness-based training and prolonged chewing intervention n =23: waiting list Participants in the intervention group significantly reduced BMI, emotional eating, external eating, and food cravings. The intervention decreased BMI, and this loss was maintained during 4 weeks of follow-up.…”
Section: Mindfulnessmentioning
confidence: 99%